Chthonic Aspects of the Pomeranian Deity Triglav and Other Tricephalic Characters in Slavic Mythology Htonski vidiki pomorjanskega boga Triglava in drugi triglavi liki v slovanski mitologiji - Trkanjec, Luka (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This article explores the nature of West Slavic deity Triglav, postulating he was primary a god of the underworld. Parallels that connect Triglav with chthonic beings from Slavic folklore are highlighted, notably dragons and serpents, and with three-headed characters of more ancient Indo-European myths.